The bumble bee microbiome increases survival of bees exposed to selenate toxicity. (14th May 2019) - Rothman, Jason A.; Leger, Laura; Graystock, Peter; Russell, Kaleigh; McFrederick, Quinn S.
Summary: Bumble bees are important and widespread insect pollinators who face many environmental challenges. For example, bees are exposed to the metalloid selenate when foraging on pollen and nectar from plants growing in contaminated soils. As it has been shown that the microbiome of animals reduces metalloid toxicity, we assayed the ability of the bee microbiome to increase survivorship against selenate challenge. We exposed uninoculated or microbiota‐inoculated Bombus impatiens workers to a field‐realistic dose of 0.75 mg l −1 selenate and found that microbiota‐inoculated bees survive slightly but significantly longer than uninoculated bees. Using 16S rRNA gene sequencing, we found that selenate exposure altered gut microbial community composition and relative abundance of specific core bacteria. We also grew two core bumble bee microbes – Snodgrassella alvi and Lactobacillus bombicola – in selenate‐spiked media and found that these bacteria grew in the tested concentrations of 0.001–10 mg l −1 selenate. Furthermore, the genomes of these microbes harbour genes involved in selenate detoxification. The bumble bee microbiome slightly increases survivorship when the host is exposed to selenate, but the specific mechanisms and colony‐level benefits under natural settings require further study.